2013
DOI: 10.1007/s12020-013-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutritional history modulates the hepatic IGF–IGFBP axis in adult male rat offspring

Abstract: Alterations in early life nutrition lead to an increased risk of obesity and metabolic syndrome in offspring. We have shown that both relative maternal undernutrition (UN) and maternal obesity result in metabolic derangements in offspring, independent of the postnatal dietary environment. Since insulin-like growth factor binding protein 2 (IGFBP2) has been shown to be independently associated with obesity and diabetes risk, we examined the IGF-IGFBP axis in male rat offspring following either maternal UN or ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 84 publications
(84 reference statements)
1
20
0
1
Order By: Relevance
“…Several studies have found that, although serum insulin does not increase, HOMA-IR increases in offspring from protein-restricted dams at 3 weeks [29] and 3 months [32]. A maternal diet with 50% of the typical digestible energy results in hyperinsulinemia in offspring at postnatal day 160 [33]. From our results, maternal chromium restriction increased body weight, impaired glucose tolerance, and led insulin resistance.…”
Section: Discussionsupporting
confidence: 49%
“…Several studies have found that, although serum insulin does not increase, HOMA-IR increases in offspring from protein-restricted dams at 3 weeks [29] and 3 months [32]. A maternal diet with 50% of the typical digestible energy results in hyperinsulinemia in offspring at postnatal day 160 [33]. From our results, maternal chromium restriction increased body weight, impaired glucose tolerance, and led insulin resistance.…”
Section: Discussionsupporting
confidence: 49%
“…44 c,d WM, Flard140YAFAT, LEP, GLU, INSHowie G.J. 73 a,b WMlard42, 140YABWSmith T. 74 WMlard42YAFAT, BW, LEP, GLU, INS, HDLPereira T.J. 75 a SDMlard84YAFAT, LEP, GLU, INSPereira T.J. 75 b SDFlard84YAFAT, GLU, INSCordero P. 76 a,b WM, Flard42YAFAT, BWSloboda D.M. 77 a,b WFlard42, 140PPPBWTsoulis M.W.…”
Section: Resultsunclassified
“…Primer sets were ß-actin forward primer CACCAACTGGGACGATATGGA and ß-actin reverse primer CAGCCTGGATGGCTACGTACAT, 188bp, accession number NM_031144 and IGF1R (commercial purchased Qiagen assay Rn_Igf1r_1_SG; catalogue # QT00178416). 13 Optimal primer conditions were adjusted to cycling conditions: length 20 bp (range 17-23 bp); Tm 63°C (range 60-65°C); and amplicon length 100-300 bp. Dissociation analyses were performed to ensure specificity, and samples producing a single peak in the dissociation curves were used.…”
Section: Rna Analysesmentioning
confidence: 99%
“…The GH-IGF axis is altered by changes in nutrition with undernutrition elevating circulating concentrations of GH but reducing the concentrations of IGF-I. 12,13 In addition, IGF-I concentrations are reduced following early-life treatment with betamethasone, typically used in management of premature birth. 14 IGF-I is a 70-amino acid peptide that is coded by the Igf1gene.…”
Section: Introductionmentioning
confidence: 99%